2015
DOI: 10.4155/bio.15.195
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apolipoprotein A-1 Quantification by LC–MS with A Silac Internal Standard Reveals Reduced Levels in Smokers

Abstract: Background Absolute quantification of protein biomarkers such as serum apolipoprotein A1 by both immunoassays and LC–MS can provide misleading results. Results Recombinant ApoA-1 internal standard was prepared using stable isotope labeling by amino acids in cell culture with [13C615N2]-lysine and [13C915N1]-tyrosine in human cells. A stable isotope dilution LC–MS method for serum ApoA-1 was validated and levels analyzed for 50 nonsmokers and 50 smokers. Conclusion The concentration of ApoA-1 in nonsmokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…Moreover, statin‐induced alterations of HDL‐associated apoA‐I and apoD also require further in‐depth investigation of functional mechanisms. The confirmed gender‐associated differences in apo concentrations as well as the impact of lifestyle factors like smoking underline the future importance of adjusted reference ranges with regards to a clinical application of apo quantification. Further confounding of plasma apo levels, which could not be addressed in this cohort, might be due to the fasting state of the investigated subjects that would presumably affect constituents of chylomicrons like apoA‐IV the most.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, statin‐induced alterations of HDL‐associated apoA‐I and apoD also require further in‐depth investigation of functional mechanisms. The confirmed gender‐associated differences in apo concentrations as well as the impact of lifestyle factors like smoking underline the future importance of adjusted reference ranges with regards to a clinical application of apo quantification. Further confounding of plasma apo levels, which could not be addressed in this cohort, might be due to the fasting state of the investigated subjects that would presumably affect constituents of chylomicrons like apoA‐IV the most.…”
Section: Discussionmentioning
confidence: 68%
“…The use of multiple peptides to target a given protein in a multiplex assay provides more evidence and selectivity for accurate quantitation. Studies have shown that, although the measured concentrations may differ among multiple peptides corresponding to a given protein, potentially reflecting differences in the efficiency of trypsin digestion or the presence of endogenous peptide modification, the correlation among them is quite good . Therefore, the selection of a representative peptide is still the chief consideration in MS‐based protein quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein and other oxidants and toxicants in smoke can cause oxidation of the thiol groups in ApoA1 (Zheng et al 2004, Shao et al 2005, Shao 2012. The literature search did not identify many studies comparing ApoA1 levels in smokers and non-smokers [one was identified in which quantification was by LC-MC and found reduced levels in smokers compared to non-smokers (Wang et al 2015)], but a number of older studies have found significant differences (Szadkowski and Myers 2008). The literature search did find a small study that investigated the effect of smoking cessation on ApoA1 levels.…”
Section: Apolipoprotein A1 (Apoa1)mentioning
confidence: 99%